DECIDE: Significantly Improved Brain MRI Results with DAC HYP versus Interferon in RRMS - Rizzo, Toni (MD Conference Express, 2014)
Daclizumab high-yield process (DAC HYP) is a humanized monoclonal antibody specific for CD25, the alpha subunit of the interleukin 2 receptor [Gold R et al. Lancet. 2013]. This article presents the magnetic resonance imaging (MRI) data from the phase 3 Efficacy and Safety of Daclizumab High Yield Process Versus Interferon β1a in Patients With Relapsing-Remitting Multiple Sclerosis trial [DECIDE; NCT01064401].